Why Atheism Remains Plausible: From Cosmology to Geography - Ji, Maisi (International Journal of Humanities and Social Science, 2026)
On 17 February 1600, Giordano Bruno, the sixteenth-century pantheist, was executed. Rejecting a transcendent deity and denying a personal God, his pantheistic view was condemned as atheistic heresy. Bruno's philosophy can be recognized as a crucial precursor to the rise of modern atheism—the explicit belief that there is no God. Historically, the Church has vehemently opposed this perspective. However, theism has gradually lost its dominant foothold across much of the Western world as scientific discoveries emerged, philosophical arguments appeared, and evidence-based research popularized. In the United States, for instance, the proportion of individuals identifying with no religious affiliation has rapidly increased from eight percent of the total population in 2000 to twenty-one percent in 2022. This secularizing trend is widely predicted to continue in the coming decades. Ultimately, one of the primary reasons for the growing presence of atheists is that the atheistic perspective remains a philosophically and scientifically plausible framework, supported by arguments ranging from cosmology to geographical distribution.